Osthole prevents acetaminophen-induced liver injury in mice - CAI Yun; SUN Wu; ZHANG Xin-xin; LIN Yan-die; CHEN Hao; LI Hao (Acta Pharmacologica Sinica, 2017)
Abstract Acetaminophen (APAP) overdose leads to severe hepatotoxicity. Osthole, a natural coumarin found in traditional Chinese medicinal herbs, has therapeutic potential in the treatment of various diseases. In this study, we investigated the effects of osthole against APAP-induced hepatotoxicity in mice. Mice were administered osthole (100 mg·kg-1·d-1, ip) for 3 d, then on the fourth day APAP (300 mg/kg, ip) was co-administered with osthole. The mice were euthanized post-APAP, their serum and livers were collected for analysis. Pretreatment with osthole significantly attenuated APAP-induced hepatocyte necrosis and the increases in ALT and AST activities. Compared with the mice treated with APAP alone, osthole pretreatment significantly reduced serum MDA levels and hepatic H2O2 levels, and improved liver GSH levels and the GSSG-to-GSH ratio. Meanwhile, osthole pretreatment markedly alleviated the APAPinduced up-regulation of inflammatory cytokines in the livers, and inhibited the expression of hepatic cytochrome P450 enzymes, but it increased the expression of hepatic UDP-glucuronosyltransferases (UGTs) and sulfotransferases (SULTs). Furthermore, osthole pretreatment reversed APAP-induced reduction of hepatic cAMP levels, but pretreatment with H89, a potent selective PKA inhibitor, failed to abolish the beneficial effect of osthole, whereas pretreatment with L-buthionine sulfoximine, a GSH synthesis inhibitor, abrogated the protective effects of osthole on APAP-induced liver injury, and abolished osthole-caused alterations in APAP-metabolizing enzymes. In cultured murine primary hepatocytes and Raw264.7 cells, however, osthole (40 μmol/L) did not alleviate APAP-induced cell death, but it significantly suppressed APAP-caused elevation of inflammatory cytokines. Collectively, we have demonstrated that osthole exerts a preventive effect against APAP-induced hepatotoxicity by inhibiting the metabolic activation of APAP and enhancing its clearance through an antioxidation mechanism.